New World Disorder : The UN after the Cold War : An Insider's view - Hanny David (London I.B. Tauris, 2008)
The end of the Cold War triggered a historic shift in world politics, and nowhere was this more keenly felt than in the United Nations. This is an insider's account of that turbulent period. Lord Hannay, who, as Britain's representative to the UN, sat in the Security Council from the time of Saddam Hussein's invasion of Kuwait until the Srebrenica massacre in Bosnia (1990-1995), gives a first hand view of events as they unfolded. Just weeks after George H.W. Bush and Mikhail Gorbachev's historic handshake, the UN was being asked to repel the Iraqi invasion of Kuwait, to wind up a string of Thi.
Include Index.
Keywords: World Politics -- United Nations